The Medium Term Impacts of Cash and In-kind Food Transfers on Learning - Avitabile, Ciro; Cunha, Jesse M.; Meilman Cohn, Ricardo (World Bank, Washington, DC, 2019)
This paper studies the medium-term impact of early-life welfare transfers on children's learning. It studies children who were exposed to the randomized controlled trial of the Mexico's Food Support Program (the Programa de Apoyo Alimentario, PAL), in which households were assigned to receive cash, in-kind food transfers, or nothing (a control). The children are matched with administrative data on primary school standardized tests, which were taken four to 10 years after the experiment began. The findings show that in-kind transfers did not impact test scores, while cash transfers led to a significant and meaningful decrease in test scores. An analysis of the mechanisms driving these results reveals that both transfers led to an increase in child labor, which is likely detrimental to learning. In-kind food transfers, however, induced a greater consumption of several key micronutrients that are vital for brain development, which likely attenuated the negative impacts of child labor on learning.